Orchard Orbweaver, Orchard Spider Leucauge argyrobapta (White), Leucauge venusta (Walckenaer) (Arachnida: Araneae: Tetragnathidae) - Donald W. Hall (EDIS, 2019)
The orchard orbweavers, Leucauge argyrobapta (White) (Figure 1) and Leucauge venusta (Walckenaer), are attractive small spiders and collectively are some of the most common spiders in the eastern U.S. The name orchard orbweaver is the common name accepted by the American Arachnological Society Committee on Common Names of Arachnids (Breen 2003) for these species, but they have also been called simply orchard spiders (Kaston & Kaston 1953, Levi & Levi 2002). Orchard orbweavers belong to the family Tetragnathidae, the longjawed orbweavers (Levi & Hormiga 2017, World Spider Catalog 2018).